Primary hepatoid adenocarcinoma of the lung with extremely elevated serum AFP: a case report and literature review - Cai, Chengsen; Zhang, Ningxin; Wang, Min; Wang, Lianzhong; Zhao, Haisu; Zhang, Xiaoye (Frontiers in Oncology, 2024)
Primary hepatoid adenocarcinoma of the lung (HAL) is an exceptionally rare subtype of lung cancer that mimics the morphology and biological behavior of hepatocellular carcinoma. Although reports in the literature are limited, HAL is known for its high malignancy and poor prognosis, thus drawing increasing attention. We present the case of a patient with a mass-like consolidation with central necrosis initially misdiagnosed as inflammation at another medical institution despite a percutaneous lung biopsy. After ineffective anti-inflammatory treatment, she was referred to our hospital. We performed another lung biopsy, obtaining five samples from different angles, and eventually diagnosed her with HAL. Surprisingly, her serum alpha-fetoprotein (AFP) levels were extraordinarily high, leading to the successful diagnosis of HAL. Here, we present a case report and a related literature review.